THE INFLUENCE OF USING DURIAN SKIN ASH AS LIME SUBSTITUTE IN GROWTH AND CROP OF CAYENNE PEPPER ON PEAT SOIL. - Saputri, Helmi; Zulfita, Dwi; Safwan, Mulyadi (Jurnal Sains Mahasiswa Pertanian, 2019)
This study aims to obtain the best durian skin ash dose in the growth and the crop of cayenne pepper on peat soil. This research began from 13 April 2019 to 05 August 2019. This research was carried at Jl. Perdana Gg Mufakat. The method used in this research was Completely Randomized Design consisted of five treatments, five repetition, and each repetition contained four plant samples. The treatment as followed: k1= 21,66 tons/ha equivalent to 433 grams/polybag, k2 = 30,84 tons/ha equivalent to 602 grams/polybag, k3 = 38,55 tons/ha equivalent to 771 grams/polybag, k4 = 47,08 tons/ha equivalent to 941 grams/polybag and k5 = 55,52 tons/ha equivalent to 1.110 grams/polybag.Â This research included durian skin ash production, seedbed media preparation, plant media preparation, ash application, planting, fertilizing, maintenance, and harvesting. The variables observed in this research were height plant (g), root volume (g), plant dry weight (g), leaf chlorophyll amount (spad unit), fruit weight (g), and the quantity of the fruit every plant. Besides that, this research observed the temperature condition(0C) and humidity (%). From this research, it can be concluded that the application of durian skin ash with dose of 38,55 tons/ ha equivalent to 771 grams/polybag is the best dose for the growth and the crop of cayenne pepper on peat soil.Key word: ash, cayenne pepper, durian skin